The need for maxillary osteotomy after primary cleft surgery: A systematic review framing a retrospective study. Issue 10 (October 2020) - Tache, Ana; Mommaerts, Maurice Y.
Abstract: Objective: This study assessed the rate of maxillary osteotomies after cleft palate surgery following a standardized two-stage palatoplasty protocol. In order to improve our treatment strategy, the results were compared with the data extracted from the literature by means of a systematic review. Design: Retrospective cohort study. Patients: Non-syndromic cleft lip, alveolus, and palate patients with complete records who underwent primary cleft palate surgery. Intervention: The incidence of midface hypoplasia after primary cleft surgery that required surgical intervention was retrospectively evaluated. Results: Of the final 51 patients included in our retrospective analysis, two required a maxillary repositioning osteotomy. The frequency was lower than reported in the literature. In the literature, there was no difference between patients treated according to a one-stage protocol (21%) and patients treated according to a two-stage protocol (20.8%), but a higher incidence of pharyngeal surgery was noted in the two-stage closure group. Only the cleft type, timing of hard palate closure, and orthodontic treatment proved to influence the need for maxillary osteotomy. Conclusion: Our protocol shows promising results and needs more validation.